ANTIOXIDANT ACTIVITY TEST OF LIDAH MERTUA (SANSEVIERIA TRIFASCIATA P.) LEAVES EXTRACT USING 1,1-DIPHENIL-2-PIKRILHIDRAZIL - Rihanah Rihanah; Minarni Rama Jura (Universitas Tadulako, 2020)
Antioxidant activity test of lidah mertua (Sansevieria trifasciata P.) leaves extract using 1,1-diphenil-2-picrylhydrazyl has been carried out. The purpose of this study was to determine the antioxidant activity of ethanol extracts of old and young leaves of lidah mertua (Sansevieria trifasciata P.). The radical concentration of 1,1-diphenil-2-picrylhydrazyl (DPPH) after the addition of ethanol extracts of old and young leaves of lidah mertua was determined using a UV-Vis spectrophotometer. The concentrations used in the ethanol extracts of old and young leaves of lidah mertua were 20 ppm, 40 ppm, 60 ppm, 80 ppm and 100 ppm. The IC50 values obtained ​​of ethanol extracts of old and young leaves of lidah mertua were 131.336 ppm and 144.568 ppm respectively, while IC50 value ​​of vitamin C as a comparison was 65.433 ppm. It can be seen that the antioxidant ethanol extracts of old and young leaves of lidah mertua are moderate compared to vitamin C.